International Comparisons of Pricing-to-Market Behavior - Knetter, Michael M. (American Economic Review, 1993)
The paper measures the degree of price discrimination across export destinations that is associated with exchange-rate changes using U.S., U.K., German, and Japanese industry-level data. Given the industries sampled, more price discrimination across destinations is observed in the U.K., German, and Japanese data. For industries that match across source countries, however, behavior is very similar across source countries. Furthermore, destination-specific price adjustment on exports to the United States from Germany and Japan is similar to price adjustment observed on shipments to other destinations. Most variation in the data appears to be related to industry.